1999
DOI: 10.1097/00001786-199910000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Designing Interdisciplinary Documentation for the Continuum of Care

Abstract: An increased emphasis on integrated care delivery and the need to access information across the care continuum led to an assessment and modification of the current documentation system at Summa Health System in Akron, Ohio. The goal was to achieve more complete and concise interdisciplinary charting. This article describes the process the two-hospital system developed to achieve integrated documentation reflecting the patient's progress toward team-defined outcomes. Steps in the evaluation and modification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Different approaches to improving documentation also have been described in the literature 16 . The move to computer‐based or non‐paper‐based documentation, with a focus on tick‐boxes and other ‘reductionistic’ techniques, will undoubtedly increase the challenge of holistic documentation and explicit decision‐making 12 . The challenge is to establish a culture of holistic decision‐making that demands documentation and the creation of software to facilitate this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different approaches to improving documentation also have been described in the literature 16 . The move to computer‐based or non‐paper‐based documentation, with a focus on tick‐boxes and other ‘reductionistic’ techniques, will undoubtedly increase the challenge of holistic documentation and explicit decision‐making 12 . The challenge is to establish a culture of holistic decision‐making that demands documentation and the creation of software to facilitate this.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these frustrations were related to the planning and documentation of medical and nursing care. Frustrations around the organization of care, which involves a range of different professional groups, have been well‐described in the literature 12,13 . Nursing staff often found themselves chasing up medical staff and acting as buffers between doctors and families when communication failed.…”
Section: Introductionmentioning
confidence: 99%
“…The review of the literature and other existing healthcare system tools revealed limited findings on the process of "interdisciplinary" care planning. Most examples were still primarily nursing focused (Brunt, 2000;Brunt, Gifford, Hart, & McQueen-Gross, 1999;Eiland, Fleshman, & Kovalchik, 2000;Gage, 1994). The opportunity for other disciplines to be actively involved was lacking.…”
Section: Processmentioning
confidence: 99%
“…In the healthcare literature, the term integration is used to describe (1) the coordination of multiple disciplines in clinical care, [3][4][5] (2) the merger of mainstream and complementary medicine, 6 (3) the use of information systems to track patients or measure quality of care, (7) (4) the incorporation of women's health issues into the medical curriculum, 8,9 or (5) various financial and organizational arrangements (horizontal or vertical integration). [10][11][12] In contrast, the CoE model defines integration as a dynamic and multidisciplinary linkage of women's health practice with research, teaching, education, community outreach, and faculty development.…”
Section: Introductionmentioning
confidence: 99%